2003
DOI: 10.1016/s0014-5793(03)00729-4
|View full text |Cite
|
Sign up to set email alerts
|

Potassium uptake in the unicellular cyanobacterium Synechocystis sp. strain PCC 6803 mainly depends on a Ktr‐like system encoded by slr1509 (ntpJ)

Abstract: The molecular basis of potassium uptake in cyanobacteria has not been elucidated. However, genes known from other bacteria to encode potassium transporters can be identi¢ed in the genome of Synechocystis sp. strain PCC 6803. Mutants defective in kdpA and ntpJ were generated and characterized to address the role of the Kdp and KtrAB systems in this strain. KtrAB is crucial for K + uptake, as the v vntpJ mutant shows slowed growth, slowed potassium uptake kinetics, and increased salt sensitivity. The v vkdpA mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
43
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 27 publications
(56 reference statements)
2
43
0
Order By: Relevance
“…Transport Activity in E. coli-Since previous reports have suggested that Synechocystis KtrB plays a role in K ϩ uptake (20,21,30), rather than in Na ϩ transport (22, 47) (www. kazusa.or.jp/cyano/), we investigated the role of Synechocystis ktr genes in K ϩ transport and analyzed the Ktr gene family.…”
Section: Three Synechocystis Ktr Gene Products Are Required For K ϩmentioning
confidence: 99%
See 2 more Smart Citations
“…Transport Activity in E. coli-Since previous reports have suggested that Synechocystis KtrB plays a role in K ϩ uptake (20,21,30), rather than in Na ϩ transport (22, 47) (www. kazusa.or.jp/cyano/), we investigated the role of Synechocystis ktr genes in K ϩ transport and analyzed the Ktr gene family.…”
Section: Three Synechocystis Ktr Gene Products Are Required For K ϩmentioning
confidence: 99%
“…During its long term adaptation to high NaCl concentrations, this organism also synthesizes and accumulates glucosylgylcerol (17)(18)(19). Determining from the genome sequence, strain PCC 6803 has been predicted to contain at least three types of K ϩ uptake systems, Kdp system, which is probably of minor importance (20), a Ktr system (21), which appears to play a role in salt stress by high NaCl concentrations (20) and K ϩ channels. However, the Ktr system has not been characterized any further.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The membrane proteins in both superfamilies share the same architecture 2,5-9 : four subunits or repeats, each with the TM-P loop-TM (where TM indicates transmembrane helix) structural motif first seen in the KcsA potassium channel structure 10 , assemble to form an ion pore with a 'selectivity filter' along its central axis. In addition, the cytosolic regulatory proteins of the Trk and Ktr transporters and of the MthK 11,12 and large-conductance Ca 2+ -gated (BK) K + channels [13][14][15] are RCK (regulate conductance of K+) domains.Ktr ion transporters are crucial K + transport systems in some bacteria 16,17 , with a role in resistance to osmotic stress and high salinity by mediating the early uptake of K + (refs 16, 18). The Ktr ion transporters are composed of two essential components 3,16 : a membrane protein (KtrB or KtrD) and a cytosolic regulatory protein (KtrA or KtrC).…”
mentioning
confidence: 99%
“…Ktr ion transporters are crucial K + transport systems in some bacteria 16,17 , with a role in resistance to osmotic stress and high salinity by mediating the early uptake of K + (refs 16, 18). The Ktr ion transporters are composed of two essential components 3,16 : a membrane protein (KtrB or KtrD) and a cytosolic regulatory protein (KtrA or KtrC).…”
mentioning
confidence: 99%